2019
DOI: 10.1186/s13034-019-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific substance use patterns and associations with individual, family, peer, and school factors in 15-year-old Portuguese adolescents: a latent class regression analysis

Abstract: Background Adolescence is a critical period of vulnerability to substance use. Recent research has shown that gender differences in adolescence substance use are complex and in constant flux. The present study aims to investigate gender differences in substance use and initiation patterns in male and female adolescents, and to assess individual, family, peer, and school associated factors of these patterns. Methods We applied latent class regression analysis to a Portug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
4
13
2
2
Order By: Relevance
“…Opposite to our finding, Turner et al demonstrated in a review that self-medication with alcohol or drugs for mood and anxiety disorders was associated with male gender [53]. A recent population-based study showed gender-specific substance use patterns among Portuguese adolescents [54]. We found increasing rates of illicit drug use among patients with ADHD for both genders, which corresponds with recent findings from the MTA longitudinal study [55].…”
Section: Discussionsupporting
confidence: 88%
“…Opposite to our finding, Turner et al demonstrated in a review that self-medication with alcohol or drugs for mood and anxiety disorders was associated with male gender [53]. A recent population-based study showed gender-specific substance use patterns among Portuguese adolescents [54]. We found increasing rates of illicit drug use among patients with ADHD for both genders, which corresponds with recent findings from the MTA longitudinal study [55].…”
Section: Discussionsupporting
confidence: 88%
“…Our results also confirm, in line with previous studies, that substance use is lower among women [58,59] and in young people who live with both biological parents [59][60][61].…”
Section: Substance Usesupporting
confidence: 93%
“…Although to our knowledge, ours is the first study to explore latent classes of drug-related beliefs in adolescents, numerous others have classified adolescents based on substance use behaviors and have subsequently explored demographic differences across classes. 21,23,24 Our findings are consistent with those of similar studies in high-income countries, particularly regarding gender and Table 4 Fit indices for latent class models age. [21][22][23] One study of high-schoolers in New Zealand found that among current drinkers, those who engaged in the highest risk behavior also held the most positive drug-related beliefs.…”
Section: Discussionsupporting
confidence: 89%
“…LCA is a modeling method that categorizes individuals based on an unobservable ''latent'' trait, using responses to more readily measure indicator variables; this type of analysis has thus far only been used in a limited way with adolescent substance use and has served primarily as a means of categorizing behavior rather than to examine how beliefs relate to real-world use. [21][22][23][24] In this study, we begin to explore beliefs as an indicator of substance use to better understand the feasibility of their use to predict future drug use in prevention programming. Conceptualizing drug-related beliefs as an underlying categorical construct may provide useful insights to help develop more effective prevention programs.…”
Section: Introductionmentioning
confidence: 99%